Analisis Kebutuhan Ruang Parkir Pada Pusat Perbelanjaan Yang Ada Di Kecamatan Medan Denai: Studi Kasus Balikado Jl. Menteng - M. Aidil Abrori; Marwan Lubis; Gunawan Tarigan (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
: Balikado is one of the shopping centers in Medan City, located on Jalan Menteng, Medan Denai District. Parking is something that is quite a concern, especially if you visit places that are busy with visitors, such as Balikado. Shopping centers usually have a busy schedule of visitors at certain times of the day, so problems occur such as not having the parking properly organized. To overcome this problem, it is necessary to identify the need for parking space. From the results of research for 7 days, (18-24 July 2023) from 09.00-18.00 WIB and data processing carried out, it can be concluded that: the largest number of vehicles entered were 71 motorbikes on Tuesday 13.00-14.00 and 31 cars on Sundays at 14.00-15.00, the largest accumulation is 77 motorbikes on Wednesdays and 25 cars on Wednesdays, the maximum parking duration is 1.68 hours for motorbikes on Sundays and the maximum parking duration is 1.82 hours for vehicles cars on Wednesdays, the largest parking volume for motorbikes is 505 vehicles on Wednesdays and cars are 174 vehicles on Sundays, the maximum parking turnover rate for motorbikes ranges from 2.29-3.68 times in 1 day and for cars range between 2.38-4.48 times in 1 day. Based on the Z value obtained of 68 SRP for motorbikes, the motorbike parking space can meet parking needs, because the available parking space is 137 SRP, Based on the Z value obtained for car is 24 SRP, then the car parking space can meet parking needs, because parking spaces are available at 39 SRP. From the research results it is clear that the parking area can meet parking needs.